Country factor behavior for integration improvement of European life insurance markets - Cummins, J. David; Rubio-Misas, María (Elsevier, 2021)
This paper provides evidence of the role that financial market development and institutional quality play in the integration of European Union (EU) life insurance markets. It analyzes ten EU life insurance markets over a seventeen-year sample period. The meta-technology cost/revenue efficiency ratios, estimated under the meta-frontier DEA framework, are used as a measure of integration and the analysis is conducted by applying Tobit panel regression models. We find that national stock market development and institutional quality enhance cost performance and integration of EU life insurance markets. Results also show that in countries where bancassurance is the main life insurance distribution channel, banking sector development contributes to integration in terms of revenue efficiency. However, we find that better outcomes in national institutional quality decrease the meta-technology revenue efficiency ratio, suggesting that life insurance prices are lower in countries with better institutions.
Keywords: Mercado financiero; Integration; Financial market development; Institutional quality; EU life insurance markets